BIOINFORMATICS PLATFORM FOR UNRAVELLING GENOMES OF POTATO AND ITS PATHOGENS - Rawat, Shashi (Potato Journal, 2019)
Bioinformatics plays a vital role in plant sciences. With the availability of large amount of data, there is a demand for tools and methods to analyse and integrate the required information at a faster pace.Â  Potato being a ploidy plant, has genetic complexity to address various functional pathways for the potato improvement including knowledge to understand how theÂ  genome as a whole works and how genes work together to direct different mechanisms like water, heat and drought stresses and tuberization in potato. By methods, software packages, and databases used in bioinformatics the relevant structural and functional information of potato can be explored which further helps in elucidating the factors responsible for improving potato varieties.Â